INOVASI KEBIJAKAN INTERNET DI ESTONIA DAN KANADA: SEBUAH PERBANDINGAN: - Sabiq, Ahmad; Kurniasih, Denok; Rosyadi, Slamet (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
This article compares internet policy innovations in Estonia and Canada, two countries with distinct geographical, social, and political characteristics in addressing the challenges of digital inclusion. Estonia has developed a comprehensive digital policy framework through initiatives such as Tiigrihüpe, e-ID, and X-Road, which have strengthened digital governance and expanded access to public services online. In contrast, Canada has focused on the development of physical infrastructure through programs like Connect to Innovate, aimed at reaching remote areas and underserved Indigenous communities. Employing a qualitative approach based on literature review, this study demonstrates that the success of internet access policies largely depends on a country's ability to formulate strategies that are adaptive to contextual challenges. Estonia has succeeded in establishing an integrated and participatory digital ecosystem, while Canada continues its efforts to bridge the geographical digital divide through infrastructure-based interventions and cross-sector collaboration. The study highlights the importance of context-sensitive and adaptive policy approaches in ensuring equitable and inclusive internet access.